2006
DOI: 10.1111/j.1526-4610.2006.00543_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Popular Sweetner Sucralose as a Migraine Trigger

Abstract: Sucralose (trichlorogalactosucrose, or better known as Splenda) is an artificial sweetener from native sucrose that was approved by the FDA on April 1, 1998 (April Fool's Day). This observation of a potential causal relationship between sucralose and migraines may be important for physicians to remember this can be a possible trigger during dietary history taking. Identifying further triggers for migraine headaches, in this case sucralose, may help alleviate some of the cost burden (through expensive medical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 3 publications
0
14
0
1
Order By: Relevance
“…Sucralose has also been associated with headache attacks, but only in isolated case reports . Bigal and Krymchantowski reported a case of a woman in which 90% of her attacks of migraine were precipitated by sucralose.…”
Section: Specific Foods Ingredients Within Foods and Beveragesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sucralose has also been associated with headache attacks, but only in isolated case reports . Bigal and Krymchantowski reported a case of a woman in which 90% of her attacks of migraine were precipitated by sucralose.…”
Section: Specific Foods Ingredients Within Foods and Beveragesmentioning
confidence: 99%
“…62 Sucralose has also been associated with headache attacks, but only in isolated case reports. 63,64 Bigal and Krymchantowski reported a case of a woman in which 90% of her attacks of migraine were precipitated by sucralose. The addition of either sucralose or sugar to orange juice demonstrated that migraine was triggered by 2/2 trials of sucralose and 0/3 trials of sugar.…”
Section: Artificial Sweetenersmentioning
confidence: 99%
“…It has no adverse effects on the central nervous system [16], immune system, reproductive performance [17,18], and red blood cells constituents and morphology [19]. Conversely, some reports suggest sucralose is a possible trigger for some migraine patients [20]. A Duke University study, found evidence that sucralose limit the bioavailability of orally administered drugs [21].…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study reported that the daily consumption of sucralose even at a lower dose (5 mg/kg body weight) for a 12-week period reduced the amount of beneficial fecal microflora, increased fecal pH and adversely modified the expression levels of several drug metabolizing factors such as P-glycoprotein 1, CYP3A4 and CYP2D1 in rats [17]. Sucralose has been also widely reported as a triggering material for migraine and headaches in a number of previous studies [18,19,20,21]. Although a number of studies have reported several adverse effects of sucralose, the subject is still controversial [15,22].…”
Section: Introductionmentioning
confidence: 99%